2010
DOI: 10.1111/j.1468-2419.2010.00360.x
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of organizational training on organizational commitment

Abstract: This empirical study investigated the impact of organizational training on employee commitment focusing on employees' emotional and affective responses towards their organization. Organizational training is conceptualized within a multidimensional framework consisting of motivation for training, access to training, benefits from training and support for training. The hypothesis of this study has been built on a resourcebased view, social exchange theory and psychological contract theory. Field research was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
3
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(178 citation statements)
references
References 61 publications
(107 reference statements)
13
150
3
12
Order By: Relevance
“…More particularly, satisfaction with training enhances normative commitment, hence increasing the readiness to transfer learning and reduce absenteeism. Part of our findings is consistent with Barlett's [54] research and the study by Bulut and Culha [59] on the relationship between a number of training-related variables (such as frequency, access, support, motivation, and rewards) and commitment to the organization. Moreover, the significant relationship between normative commitment to the organization on the one hand, and readiness to transfer learning and absenteeism on the other, indicates the impact of the training on the individual, which, in addition, is favorable to the organization in terms of employee willingness to harness learning, and to reduce cognitive or attitudinal withdrawal such as absenteeism, which jeopardizes investment in training.…”
Section: Implications For Researchsupporting
confidence: 80%
“…More particularly, satisfaction with training enhances normative commitment, hence increasing the readiness to transfer learning and reduce absenteeism. Part of our findings is consistent with Barlett's [54] research and the study by Bulut and Culha [59] on the relationship between a number of training-related variables (such as frequency, access, support, motivation, and rewards) and commitment to the organization. Moreover, the significant relationship between normative commitment to the organization on the one hand, and readiness to transfer learning and absenteeism on the other, indicates the impact of the training on the individual, which, in addition, is favorable to the organization in terms of employee willingness to harness learning, and to reduce cognitive or attitudinal withdrawal such as absenteeism, which jeopardizes investment in training.…”
Section: Implications For Researchsupporting
confidence: 80%
“…For example, Gürbüz's Study (2007) concluded with a positive relations hip between job satisfaction and education level in a case of 600 employees working in 30 fourand five-star hotels located in several major cities in Turkey. Similarly, Bulut and Culha (2010) used a survey data of 298 participants of four-and five-star hotels operating in Izmir-Turke y and found that all dimensions of training, namely motivation for training, access to training, benefits from training, and support for training had been leading to increases in employee commitment which is closely linked to high job satisfaction.…”
Section: Using the Administrative Data Set Of European Working Conditmentioning
confidence: 99%
“…Hence, educational training in hotels can be regarded as a multi-dimensional framework, including training motivation, training acquisition, training benefit, and training support. The results demonstrated that all such measures positively influence organizational commitment [6].…”
Section: Educational Training System Of International Hotelsmentioning
confidence: 63%